4‐Styrenesulfonyl‐(2‐methyl)aziridine: The First Bivalent Aziridine‐Monomer for Anionic and Radical Polymerization. Issue 1 (24th May 2017) - Gleede, Tassilo; Rieger, Elisabeth; Homann‐Müller, Tatjana; Wurm, Frederik R.
Abstract: 4‐Styrenesulfonyl‐(2‐methyl)aziridine (StMAz), the first orthogonal aziridine monomer, for both anionic ring‐opening and radical polymerization is presented. Both polymerization pathways are accessible without using protective groups. Aza‐anionic ring‐opening polymerization (A‐AROP) of StMAz and other methyl‐aziridine derivatives provide multifunctional polyaziridines. Molecular weights between 3000 and 13 000 g mol −1 are obtained with low molecular weight dispersities ( Ð = 1.1). The amount of vinyl groups in linear polyaziridines from A‐AROP depends on the monomer/comonomer ratio. The vinyl groups of P(StMAz)‐ homo‐ or copolymers are entirely convertible by thiol‐ene addition. This allows modification with multiple functional groups. Free radical polymerization of StMAz leads to polyalkylenes with aziridine side groups, which are known to be efficiently addressable via nucleophiles. Polysulfonamides still belong to a rather new class of polymers accessible by anionic polymerization. Enlarging the scope of postpolymerization modifications on polyaziridines/‐sulfonamides is important for further macromolecular architectures. The aziridine and the vinyl group are combined to develop the first orthogonal monomer for aza‐anionic polymerization and radical polymerization. Abstract : The first bivalent aziridine for the anionic ring‐opening and radical vinyl polymerization is presented. Postpolymerization modifications of pendant vinyls or aziridines allow for the preparation of poly(ethylene imine)‐ and poly(alkylene)‐derivatives by orthogonal chemistry or thermal cross‐linking.